Pahiyas San Isidro ritual as tradition and touristic festival - Tan, Pearl E. (2009)
This study elucidates three intertwining aspects of the Pahiyas of Lucban, Quezon: ritual, touristic festival, and tradition. Reconfiguring the practice of the San Isidro through negotiative and creative performance of the Pahiyas reveals both continuity and changes in the transmission of processes and products. This has been largely due to changes in the motivations of the performers of the Pahiyas in response to changing social conditions, particularly the intervention of tourism in the ritualistic tradition. Implicated in the touristic development are the ways by which the Lukbanins define their local identity through authentication of their tradition, emblemization of the Pahiyas, and reflexive representation of themselves. The Pahiyas shows that ritual and tradition are constituted as they are performed. The agentive performance of the Pahiyas has departed from the simple, mainly religious practice of the San Isidro in favor of a dynamic, interactive, creative appropriation of tourism and commerce that heightens the development of the aesthetic sensibility and skills of the Lukbanins.